Mutation Update for Kabuki Syndrome Genes KMT2D and KDM6A and Further Delineation of X‐Linked Kabuki Syndrome Subtype 2. Issue 9 (7th July 2016) - Bögershausen, Nina; Gatinois, Vincent; Riehmer, Vera; Kayserili, Hülya; Becker, Jutta; Thoenes, Michaela; Simsek‐Kiper, Pelin Özlem; Barat‐Houari, Mouna; Elcioglu, Nursel H.; Wieczorek, Dagmar; Tinschert, Sigrid; Sarrabay, Guillaume; et al.
Abstract : Kabuki syndrome is a rare genetic condition that is caused by mutations in the KMT2D gene in approximately 56%–75% of cases and by mutations in KDM6A in 5%–8%. We present a mutation screening of 347 patients with Kabuki syndrome, which identified 208 mutations in KMT2D, as well as twelve novel KDM6A mutations. We discuss the molecular and clinical findings in this large cohort and compare them to the literature with a focus on the rarer X‐linked Kabuki syndrome type 2. ABSTRACT: Kabuki syndrome (KS) is a rare but recognizable condition that consists of a characteristic face, short stature, various organ malformations, and a variable degree of intellectual disability. Mutations in KMT2D have been identified as the main cause for KS, whereas mutations in KDM6A are a much less frequent cause. Here, we report a mutation screening in a case series of 347 unpublished patients, in which we identified 12 novel KDM6A mutations (KS type 2) and 208 mutations in KMT2D (KS type 1), 132 of them novel. Two of the KDM6A mutations were maternally inherited and nine were shown to be de novo. We give an up‐to‐date overview of all published mutations for the two KS genes and point out possible mutation hot spots and strategies for molecular genetic testing. We also report the clinical details for 11 patients with KS type 2, summarize the published clinical information, specifically with a focus on the less well‐defined X‐linked KS type 2, and comment on phenotype–genotype correlations as well as sex‐specific phenotypic differences. Finally, we also discuss a possible role of KDM6A in Kabuki‐like Turner syndrome and report a mutation screening of KDM6C ( UTY ) in male KS patients.